2018
DOI: 10.1097/yco.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

New findings in pharmacogenetics of schizophrenia

Abstract: The findings to date are promising and provide us a better understanding of the development of side effects and response to antipsychotics. However, more comprehensive investigations in large, well characterized samples will bring us closer to clinically actionable findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 182 publications
2
31
0
1
Order By: Relevance
“…HLA-C*06:02-negative patients respond better to adalimumab than ustekinumab [36,37]. Other examples of NCDs which involve the use of GB for diagnosis or choice of therapy include cardiovascular disorders, diabetes, Parkinson's disease, age-related macular degeneration, inflammatory bowel diseases, autism spectrum disorder, and schizophrenia (Table 1) [38][39][40][41][42][43][44]. These examples are set to increase in the coming years according to the discovery of rare alleles [45].…”
Section: Genomic Biomarkers In Ncdsmentioning
confidence: 99%
“…HLA-C*06:02-negative patients respond better to adalimumab than ustekinumab [36,37]. Other examples of NCDs which involve the use of GB for diagnosis or choice of therapy include cardiovascular disorders, diabetes, Parkinson's disease, age-related macular degeneration, inflammatory bowel diseases, autism spectrum disorder, and schizophrenia (Table 1) [38][39][40][41][42][43][44]. These examples are set to increase in the coming years according to the discovery of rare alleles [45].…”
Section: Genomic Biomarkers In Ncdsmentioning
confidence: 99%
“…We designed synthetic probes for NGS, targeting genes associated with dementia, SCZ, and several pharmacogenetic targets. The selection of genes was based on a literature search for published works reporting an effect of common variations or rare variants in SCZ, dementia or drug response to different antipsychotics or antidementia drugs 6,7,[26][27][28][29][30][31][32][33][34][35][36] ; a list of the captured genes is reported in Supplementary Table 1. Gene capture was performed using the Haloplex target enrichment system (Agilent Technologies, USA) with 1.51Mb with 40754 amplicons.…”
Section: Targeted Ngsmentioning
confidence: 99%
“…The large variability can be attributed to a variety of complex factors, in which genetic factors may play a dominant role. Numerous studies on pharmacogenomics have been conducted to elucidate gene variants related to antipsychoticinduced weight gain or metabolic disturbances (Lett et al, 2011;Zhang et al, 2016;Zai et al, 2018). A meta-analysis has revealed that the genes of pharmacodynamic targets of antipsychotics like HTR2C, DRD2, ADRA2A and genes implicated in obesity such as MC4R, GNB3, FTO, LEP, LEPR, BDNF, and INSIG2 seem to be consistently relevant to antipsychotic-induced weight gain (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%